(untitled) (Journal of Computational Mathematics, 2004)
We study a class of blockwise waveform relaxation methods, and investigate its convergence properties in both asymptotic and monotone senses. In addition, the monotone convergence rates between different pointwise/blockwise waveform relaxation methods resulted from different matrix splittings, and those between the pointwise and blockwise waveform relaxation methods are discussed in depth.